Study of oxygen vacancies motion in BST thin film - Wu, Ruihong. (2009)
Barium strontium titanate (BST) films with high dielectric constant have attracted great attention for applications in capacitors and dynamic random access memory (DRAM). To increase the reliability of the BST capacitors, it is very important to minimize leakage current to preserve information stored as electron charges. Oxygen vacancies generated during fabrication of the devices are believed to contribute greatly to the leakage current. Many studies have been carried out on the effects of oxygen vacancies on leakage current. Further study on the redistribution of oxygen vacancies under electric field stress is still needed. In this project, we first studied on the I-V and C-V behaviors of sol-gel derived BST thin film before and after dc bias stressing. It is found that after dc stressing, the negative and positive regions of an I-V curve will change in opposite direction, where one increases and the other decreases. C-V curve shows a general lowering and curve shifting after dc bias stressing. These are explained by moving of oxygen vacancies, causing changes in the interface schottky barrier, internal field, and so on. Further study was carried out to characterize oxygen vacancies redistribution profile by employing EFM. This is relatively new in the study of this field. From EFM scanning results, it is found oxygen vacancies redistribution profile complies with that predicted from I-V and C-V measurements. This would definitely help in understanding how oxygen vacancies affect the leakage current, as well as providing potential ways of minimizing leakage current in BST thin film capacitors.